The Impact of Climate Change on the Nigerian Economy - Ogbuabor, Jonathan E.; Egwuchukwu, Emmanuel I. (International Journal of Energy Economics and Policy, 2017)
This paper examined the impact of climate change on the overall growth of the Nigerian economy. The OLS estimation technique and data for the period 1981 to 2014 were used. Changes in annual rainfall, carbon emission and forest depletion were used to capture climate change, while changes in government expenditure, domestic private investment and exchange rate were used as control variables. The results indicate that both in the long-run and short-run, carbon emissions affect growth adversely. In addition, forest depletion impacts negatively on growth in the short-run. These results imply that Nigerian government should evolve and implement policies to curb carbon emissions and forest depletion. In particular, a National Climate Change Commission is required in Nigeria to deal with all climate change issues. Furthermore, the finding that domestic private investment and naira-to-dollar exchange rate impede growth in Nigeria means that policymakers and governments at all levels in Nigeria should evolve and implement policies to reverse these undesirable outcomes. Keywords: Climate Change; Economic Growth; Ordinary Least Squares; Nigeria JEL Classifications: Q25; O40; C22; N17